EXAMPLES OF TRANSPORT ORGANIZATION DURING THE EVENTS OF MASS NATURE (Perner's Contacts, 2011)
Article follows the author's previous article Analyse of transport organization during the events of mass nature in Hradec Králové, published in Perner's Contacts 3/2010. It deals with the transport organization on the events of mass nature in other selected Czech cities. The second part of the article deals with examples of the transport organization (especially the shuttle) abroad.
Keywords: Events of mass nature; Brno; shuttle; Leeds; transport organization; passenger transport; Ostrava; Richmond